STUDY OF CÁTODOS TYPE NAMF3 (M: CO, NI, MN) - Guzman D., A. (2012)
In the present work there describes a series of synthesis of materials type NaMF3 using salts of Co, Ni and Mn as precursors, for use as positive electrodes in lithium battery, which uses lithium as the negative electrode. The synthesis product obtained was characterized with structurally DRX, the particle size distribution was observed by scanning electron microscope. For the electrochemical study was assembled a stack type CR2032 which was carried out studies of cyclical behavior of loading and unloading to check if it behaves like a secondary battery. The results obtained show be this synthesis method proposed is a quick and easy method for obtaining this type of cathodes